Exposure-effect relationship of mycophenolic acid and prednisolone in adult patients with lupus nephritis - Abd. Rahman, Nurul Azrin; Tett, Susan E.; Abdul Gafor, Abdul Halim; McWhinney, Brett; Staatz, Christine E. (John Wiley & Sons, Inc., 2015)
The aim was to examine relationships between total and unbound mycophenolic acid (MPA) and prednisolone exposure and clinical outcomes in patients with lupus nephritis. METHODS: Six blood samples were drawn pre- and at 1, 2, 4, 6 and 8 h post-dose and total and unbound MPA and prednisolone pre-dose (C0 ), maximum concentration (Cmax ) and area under the concentration-time curve (AUC) were determined using non-compartmental analysis in 25 patients. The analyses evaluated drug exposures in relation to treatment response since starting MPA and drug-related adverse events. RESULTS: Dose-normalized AUC varied 10-, 8-, 7- and 19-fold for total MPA, unbound MPA, total prednisolone and unbound prednisolone, respectively. Median values (95% CI) of total MPA AUC(0,8 h) (21.5 [15.0, 42.0] vs. 11.2 [4.8, 30.0] mg l-1 h, P= 0.048) and Cmax (11.9 [6.7, 26.3] vs. 6.1 [1.6, 9.2] mg l-1 , P = 0.016) were significantly higher in responders than non-responders. Anaemia was significantly associated with higher total (37.8 [14.1, 77.5] vs. 18.5 [11.7, 32.7] mg l-1 h, P = 0.038) and unbound MPA AUC(0,12 h) (751 [214, 830] vs. 227 [151, 389] mg l-1 h, P = 0.004). Unbound prednisolone AUC(0,24 h) was significantly higher in patients with Cushingoid appearance (unbound: 1372 [1242, 1774] vs. 846 [528, 1049] nmol l-1 h, P = 0.019) than in those without. Poorer treatment response was observed in patients with lowest tertile exposure to both total MPA and prednisolone as compared with patients with middle and higher tertile exposure (17% vs. 74%, P = 0.023). CONCLUSIONS: This study suggests a potential role for therapeutic drug monitoring in individualizing immunosuppressant therapy in patients with lupus nephritis.